Anatomy and Histology of Digestive Tract in Melanophila (Trachypteris) picta decastigma (Fabricius, 1787) (Coleoptera: Buprestidae) - Nurcan Özyurt Koçakoğlu; Üzeyir Çağlar; Selami Candan (European Journal of Biology)
Objective: The aim of this study is to investigate the anatomy and histology of Melanophila picta decastigma (Fabricius) (Coleoptera: Buprestidae). Materials and Methods: Some of the samples were fixed in 10% formaldehyde for light microscopy, others were fixed with 2.5% glutaraldehyde for scanning electron microscopy (SEM). Then the samples were examined by using stereo, light, and SEM. Results: The digestive tract in M. picta decastigma consists of foregut, midgut, and hindgut. The foregut is composed of the pharynx, esophagus, crop and proventriculus. The foregut showed muscle layers followed by intima and epithelium. There is a long, tubular pair of gastric caeca in the anterior part of the midgut. In cross-sections, a single-layered cylindrical epithelium with a short striated border. The midgut showed that the epithelial lining was substantially folded, giving its lumen a curved profile. These monolayered columnar epithelial cells had their nuclei located medially, and apically they have a striated border. The midgut surface was covered by rounded structures called regenerative crypts. The main sections of hindgut (pyloric valve, ileum, colon and rectum) were clearly observed. In the hindgut sections, there appeared to be a highly folded cuticular lining, a monolayer cubic epithelium and a very muscular wall. Conclusions: Studies on the digestive tract histo-anatomy of M. picta decastigma will add more information to assist in experimental, taxonomical, histological, and anatomical studies about insect tissues and will serve as a basis for control studies.